Coating performances of copolymers from a novel palm oil-based macromer and methyl methacrylate - Ataei, S.; Yahya, Rosiyah; Gan, S.N. (Emerald, 2012)
Purpose - The purpose of this paper is to develop hybrid copolymers through the copolymerisation of a novel low molecular weight oleic acid-based macromer with methyl methacrylate (MMA), with the aim of combining the good properties of alkyd and acrylic binders. Design/methodology/approach - The macromer was synthesised from phthalic anhydride, oleic acid and glycerol. It was copolymerised with MMA using a free radical initiator. The ratio of the macromer and MMA was varied and the glass transition temperature, molecular weight, thermal stability, and film properties of the copolymers were characterised. Findings - Under similar conditions of temperature and reaction time, the lower macromer to MMA ratio has led to faster polymerisation rate, higher molecular weight and higher T g of the copolymer. Generally, all the coatings showed excellent adhesion properties, while the coatings with the higher content of MMA exhibited better alkali and water resistance. Research limitations/implications - The macromer used in the present context was synthesised from oleic acid and glycerol supplied by a local palm oil oleochemicals manufacturer. Presumably the same raw materials from other vegetable oils could also be used. In addition, the macromer structure could be changed by varying the formulation so that it would have different molecular weight and functionality. Practical implications - The method has managed to combine the properties of alkyd and acrylic, resulting in coatings that exhibit good mechanical and chemical properties, fast physical drying as well as excellent adhesion. Originality/value - Oleic acid and glycerol are palm oil derivatives which are from natural resources and are sustainable raw materials. Although the macromer by itself cannot air-dry due low iodine value, this could be overcome through copolymerisation with methyl methacrylate to find numerous applications in surface coating.